Blood biochemical parameters in mice under the action of polyphosphate esters and their complexes with antibiotics - M. R. Kozak; I. M. Petruh (Біологія тварин, 2023)
Complexes of polyphosphate esters with antibiotics were developed in Lviv Polytechnic National University together with scientists of Institute of Animal Biology NAAS to reduce the negative impact of antibiotics on the animal body. The conducted experiments allow assessing the effect of antibiotics, polyphosphate esters and complexes of polyphosphate esters with antibiotics on the body of laboratory animals based on biochemical markers of hepato- and nephrotoxicity. The antibiotics were administered in average daily therapeutic doses. It was found that the physiological state of mice and their blood biochemical indicators were within physiological normal values after the administration of polyphosphate ester P4 and complexes of polyphosphate ester P4+antibiotics (amoxicillin, oxytetracycline, and doxycycline). At the same time, intramuscular administration of polyphosphate ester P6 and complexes of P6+antibiotics have a certain negative effect on mice, which is manifested by changes in the activity of marker enzymes: aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP). We found an increase in AST and ALT activities. P6+amoxicillin and P6+oxytetracycline complexes increased ALP activity. Complexes P4+antibiotics decreased ALP. Blood urea content decreased after the administration of polyphosphate ester P6 by 38.5%, P6+oxytetracycline by 26.9%, P6+doxycillin by 21.8%. P6+amoxicillin complex caused a significant increase by 237% in the concentration of creatinine in the blood of mice. The changes of blood creatinine concentration of other experimental groups fell within normal physiological range. Conducted studies of blood biochemical characteristics of mice under the action of new complexes of nanobiopolymer transporters with antibiotics ensured the selection of antibacterial drugs with low toxicity.